Optimization Of Law Enforcement In Traffic Accident Cases To Increase Justice And Road Safety - Ahmad Syahputra; Erniyanti Erniyanti; Ramlan Ramlan (International Journal of Social Welfare and Family Law, 2024)
Traffic accident law enforcement is a crucial element in efforts to improve justice and road safety in Indonesia. In the jurisdiction of the Tanjung Pinang Police, the problem of traffic accidents is a serious concern considering the high number of accidents that occur every year. This study aims to identify obstacles that hinder the optimization of traffic accident law enforcement and formulate effective solutions to overcome these obstacles. The research method used is a qualitative method with a case study approach. Data was collected through in-depth interviews with law enforcement officials, document analysis, and direct observation on the ground. Data analysis was carried out descriptively to understand the dynamics of traffic accident law enforcement in this region. The results of the study show that there are four main obstacles in traffic accident law enforcement at the Tanjung Pinang Police: limited human resources and equipment, lack of socialization and education about traffic safety, legal culture that has not been well formed in the community, and coordination between law enforcement agencies that is not optimal. Limited resources cause case handling to be less efficient, while the lack of socialization and education results in low public awareness of the importance of obeying traffic rules. In addition, the weak legal culture makes people reluctant to report accidents or provide information as witnesses. Poor coordination between the police, prosecutor's office, and the courts slows down the case resolution process. To overcome these obstacles, this study suggests increasing the allocation of resources and ongoing training for law enforcement officials, intensifying education and socialization programs on traffic safety to the public, applying a restorative justice approach to build public trust in the law, as well as the formation of joint working teams and the use of integrated information systems to improve coordination between institutions. With these steps, it is hoped that traffic accident law enforcement can run more effectively and efficiently, so that justice and road safety in Tanjung Pinang can be achieved.